Heat conduction in functionally graded material - Wong, Thomas Jin Her (Nanyang Technological University, 2023)
This report investigates heat conduction in Functionally Graded Materials (FGMs) using the Boundary Element Method (BEM). FGMs, known for their spatially variable properties, are crucial in environments with extreme thermal conditions. This report explores heat conduction principles and introduces BEM as an effective numerical method for analysing complex geometries, particularly suited for FGMs. Using a MATLAB-based BEM framework, the report analyses the thermal behaviour of FGMs with the aim to enhance the understanding of FGMs' heat conduction, at the same time presenting BEM's accuracy and efficiency. The findings provide insights into the thermal management of FGMs, with implications for their practical application in various industries. The report concludes with future research directions, emphasizing the importance of experimental validation and the exploration of transient heat conduction.